Perbandingan Peramalan Jumlah Produksi Air Bersih PT. Air Minum Giri Menang dengan Metode Double Exponential Smoothing dari Holt dan Brown menggunakan Optimasi Algoritma Kuadratik - Pazira, Era; Zulhan Widya Baskara; Aini, Qurratul; Zulhan Widya Baskara (Universitas Mataram, 2024)
Regional Water Supply Companies (PDAM) play a crucial role in ensuring the availability of clean and consumable water. This study aims to compare the Double Exponential Smoothing (DES) methods—Brown’s one-parameter and Holt’s two-parameter—for forecasting the clean water production of PT. Air Minum Giri Menang (Perseroda), emphasizing parameter optimization using a quadratic algorithm. The algorithm efficiently determines the optimal smoothing parameters to minimize forecasting errors measured by the Mean Absolute Percentage Error (MAPE). The results indicate that Brown’s DES method, with a MAPE of 3.29%, outperforms Holt’s DES method, which has a MAPE of 3.96%. While both methods are highly accurate for forecasting (MAPE ≤ 10%), the quadratic algorithm optimization makes Brown’s DES method the preferred choice for planning clean water production for the January–June 2023 period.